Cumbia! scenes of a migrant Latin American music genre - Fernández l'Hoeste, Héctor D. 1962-; Vila, Pablo 1952- (Duke University Press, 2013)
Cumbia music in Colombia: origins, transformations, and evolution of a coastal music genre / Leonardo D'Amico -- ¿Pa' dónde vas Marioneta? ¿Pa' donde va la gaita? : la Cumbiamba Eneyé returns to San Jacinto / Jorge Arévalo Mateus with Martín Vejarano -- Cumbia in Mexico's northeastern region / José Juan Olvera Gudiño -- Rigo Tovar, cumbia, and the transnational grupero boom / Alejandro L. Madrid -- Communicating the collective imagination : the socio-spatial world of the Mexican sonidero in Puebla, New York and New Jersey / Cathy Ragland -- From the world of the poor to the beaches of Eisha : cumbia, and the search for a popular subject in Peru / Joshua Tucker -- Pandillar in the jungle : regionalism and tecno-cumbia in Amazonian Peru / Kathryn Metz -- Gender tensions in Cumbia villera's lyrics / Pablo Semán and Pablo Vila -- Feliz, feliz / Cristian Alarcón -- El "tú" tropical, el "vos" villero, and places in between : language ideology, music, and the spatialization of difference in Uruguay / Matthew J. Van Hoose -- On music and Colombianess : towards a critique of the history of cumbia / Héctor Fernández L'Hoeste
Includes bibliographical references and index. - Description based on print version record
Keywords: Cumbia (Music) / History and criticism / America; Working class / Songs and music / History and criticism / America; Musiksoziologie; Cumbia; Amerika; Aufsatzsammlung